2002
DOI: 10.1210/jcem.87.5.8481
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-Suppressive Therapy in Girls with Early and Fast Puberty Affects the Pace of Puberty but Not Total Pubertal Growth or Final Height

Abstract: Early and fast puberty (EFP) in girls, defined as pubertal onset at age 8-9 yr, with an accelerated course, may cause compromised final height (FHt) and psychosocial distress. Treatment with a gonadotropin-suppressive agent is controversial, because the improvement in FHt is equivocal and there may be risk of obesity. We analyzed the data of 126 girls with EFP: 63 treated with GnRH analog (GnRHA) since Tanner stage 3, for 2-4 yr; and 63 untreated. Age at onset of puberty; accelerated time of transition from Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 35 publications
2
51
1
5
Order By: Relevance
“…Conversely, CPP diagnosed after the age of 6 yr had reduced post treatment height gain and compromised final height, probably due to pre treatment intrinsic changes in the growth plate according Lazar and cols. (24,47). In a Brazilian study involving 45 girls, we found no significant association between chronological age at the start of therapy and posttreatment linear growth (42).…”
Section: Long-term Follow-upcontrasting
confidence: 61%
See 3 more Smart Citations
“…Conversely, CPP diagnosed after the age of 6 yr had reduced post treatment height gain and compromised final height, probably due to pre treatment intrinsic changes in the growth plate according Lazar and cols. (24,47). In a Brazilian study involving 45 girls, we found no significant association between chronological age at the start of therapy and posttreatment linear growth (42).…”
Section: Long-term Follow-upcontrasting
confidence: 61%
“…In fact, the main factors determining normal final height in girls with CPP treated with depot GnRHa were shorter interval between the onset of puberty and onset of therapy, higher height SDS at the onset and end of therapy, and target height (42). Finally, no benefits on final height was demonstrated in those girls with early or fast puberty, although benefits on psychosocial profile and in delay menarche should be considered (24,44,47). Transitional changes in body composition and bone mass may occur without consequences in adulthood (44,47,59).…”
Section: Long-term Follow-upmentioning
confidence: 94%
See 2 more Smart Citations
“…In addition, other studies in children with 'premature' or 'early' puberty and decreased predicted height have made similar observations, i.e. that short treatments with GnRH agonists led to no or clinically insignificant adult height gains (19,22,23). This is reminiscent of the increased adult height of patients with hypogonadism, only if untreated to the age of 20 years (24).…”
Section: Gonadotropin-releasing Hormone (Gnrh) Agonists In Short Chilmentioning
confidence: 55%